2020
DOI: 10.1371/journal.ppat.1009181
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of 8,839 Clostridioides difficile genomes reveals recombination-driven evolution and diversification of toxin A and B

Abstract: Clostridioides difficile is the major worldwide cause of antibiotic-associated gastrointestinal infection. A pathogenicity locus (PaLoc) encoding one or two homologous toxins, toxin A (TcdA) and toxin B (TcdB), is essential for C. difficile pathogenicity. However, toxin sequence variation poses major challenges for the development of diagnostic assays, therapeutics, and vaccines. Here, we present a comprehensive phylogenomic analysis of 8,839 C. difficile strains and their toxins including 6,492 genomes that w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 91 publications
(147 reference statements)
2
59
1
Order By: Relevance
“…However, the need for bezlotoxumab to simultaneously occupy two epitopes in TcdB in order to be effective also increases its susceptibility to residue changes in TcdB variants. Epitope-1 and -2 in TcdB each consists of about 20 amino acids, and variations have been observed in many TcdB variants especially in epitope-1 16 , 20 (Supplementary Fig. 10d, e ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the need for bezlotoxumab to simultaneously occupy two epitopes in TcdB in order to be effective also increases its susceptibility to residue changes in TcdB variants. Epitope-1 and -2 in TcdB each consists of about 20 amino acids, and variations have been observed in many TcdB variants especially in epitope-1 16 , 20 (Supplementary Fig. 10d, e ).…”
Section: Resultsmentioning
confidence: 99%
“…These amino acid substitutions in the bezlotoxumab-binding epitopes are believed to decrease the binding affinities and neutralization potencies of bezlotoxumab 20 . For example, the neutralization efficacy of bezlotoxumab on TcdB2 is ~200-fold lower than TcdB1 16 , 19 . Consistently, we found that bezlotoxumab showed a much lower potency in blocking TcdB2 on HeLa cells compared with TcdB1 in the cell-rounding assay, and its Fab failed to show any protection at the highest concentration tested (2 µM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations